Peningkatan Kemampuan Menjahit Masyarakat Melalui Pembuatan “Tote Bag” Di Desa Bukit Sakai Kecamatan Kampar Kiri - Zariul Antosa; Adelia Syahputri; Darisman Henki Shaputra; Desi Maryani; Febrika Anwar; Frisilia Febriyanti; Muhamad Ridwan; M. Rafiqul A’la; Muhana Firza Nabilla; Rini Pratiwi; Winzila Mahfuzah (Yayasan Kajian Riset Dan Pengembangan Radisi, 2022)
The purpose of this service is to introduce the technique of sewing bags using a sewing machine to the local community as a business opportunity by utilizing materials from the surrounding environment. In this service, a tote bag is made from canvas material combined with batik patterned fabric. The method used in this service activity is by surveying Hamlet II in Bukit Sakai Village, then holding practices as well as training carried out in collaboration with the women in the village. The trainees participated in this activity with enthusiasm and enthusiasm. The result of this tote bag making training is because it adds to the knowledge of the Bukit Sakai Village training participants to be made into handicrafts that are traded and traded, and hopes that this activity can continue or not just this one time. With this training, trainees will gain knowledge or skills that are useful for improving the family economy